Techonology-Based Human Resource Management as a Strategy for Improving the Competence of Public High School Teachers in Jambi City - Ashira Naila Susanti; Ananda Clarissa; Callista Putri Andani; Devi Riani; Muthia Salsabila (IECON: International Economics and Business Conference, 2025)
This study aims to analyze the implementation of technology-based human resource management (HRM) as a strategy to improve the competence of public high school teachers in Jambi City using a qualitative approach through in-depth interviews with principals, teachers, and HR management staff. The results show that the integration of technology, such as the use of Management Information Systems (MIS) and Learning Management Systems (LMS), has facilitated data management, online training, and digital collaboration among teachers, thereby supporting administrative efficiency, objective recruitment, and flexible competency development. However, main challenges faced include limited technological infrastructure, low digital literacy among some teachers, and lack of basic technological training for senior teachers. Institutional support, availability of facilities, and participative policies are key success factors, while disparities in technology access remain significant obstacles. The study recommends optimizing digital infrastructure, continuous training, and strengthening policies on technology-based HR development to ensure sustainable and relevant improvements in teacher competence aligned with educational needs in the digital era.